2020
DOI: 10.1007/s13187-020-01850-x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating a Transition Workbook for Childhood Cancer Survivors: a Pilot Study

Abstract: Many childhood cancer survivors (CCS) could benefit from improved knowledge about their cancer diagnosis, the treatments received, and associated risks during the period when they transition into adult aftercare. Interventions that support the transition from pediatric to adult care have showed high patient satisfaction. We developed an educational workbook, "Life After the Janeway," to support CCS transition into adult care. We evaluated its understandability, actionability, and overall acceptability, using a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(18 citation statements)
references
References 16 publications
(34 reference statements)
1
16
0
Order By: Relevance
“…One of the motivations for the project was that we all felt there were potential gaps in the transition programs for young adults with ED, potentially leading to disruptions in care and adverse outcomes for these patients. RC had recently completed a project with survivors of childhood cancer, where patients requested a locally relevant, age-appropriate educational resource to support their transition into adult care [ 20 ]. At the start of the project, the research team felt that a similar resource for patients with ED would likely be useful.…”
Section: Methodsmentioning
confidence: 99%
“…One of the motivations for the project was that we all felt there were potential gaps in the transition programs for young adults with ED, potentially leading to disruptions in care and adverse outcomes for these patients. RC had recently completed a project with survivors of childhood cancer, where patients requested a locally relevant, age-appropriate educational resource to support their transition into adult care [ 20 ]. At the start of the project, the research team felt that a similar resource for patients with ED would likely be useful.…”
Section: Methodsmentioning
confidence: 99%
“…Then, 1267 were removed after applying the inclusion criteria, and the full texts of the remaining 63 articles were screened. Finally, nine studies met the inclusion criteria: four pilot studies [11,[28][29][30], three single-arm pre-post studies [31][32][33], one case series [34], and one developmental study [35]. Six trials were undertaken in the USA [28,29,31,[33][34][35], one in Canada [11], one in the Netherlands [32], and one in Germany [30].…”
Section: Included Studiesmentioning
confidence: 99%
“…In addition, the physical, sexual, psychological, emotional, and management skills [9]. In addition, the physical, sexual, psychological, emotional, cognitive, and social changes and the challenges of managing their future care also make the transition phase a period of major stress and unfavorable consequences [10,11]. CCSs who are going through the transition period may experience an interruption in their medical follow-up, the emergence of medical complications, or the deterioration of their general health [12].…”
Section: Introductionmentioning
confidence: 99%
“…We conducted a scoping review to summarise the features of intervention components of the current transition studies for CCSs. All original studies (n=9) that investigated transition interventions in CCSs were included 15–23. Current studies identified essential elements for a transition programme, such as delivering knowledge, developing skills of coordination of care and addressing psychosocial needs.…”
Section: Introductionmentioning
confidence: 99%
“…Researchers in current studies experimented on the traditional delivery format in limited transitional interventions, such as workbooks15 16 and face-to-face consultation 17 19 22. Robust web-based interventional and evaluative strategies in the transition of CCSs have yet to be developed,29 although existing evidence suggests that these interventions are broadly acceptable by CCSs and can derive benefits from them 30.…”
Section: Introductionmentioning
confidence: 99%